Systems modelling as an approach for eliciting the mechanisms for hip fracture recovery among older adults in a participatory stakeholder engagement setting - Ansah, John Pastor; Chia, Aloysius Wei-Yan; Koh, Vanessa Jean Wen; Lai, Wei Xuan; Koh, Joyce Suang Bee; Goh, Kiat Sern; Yeo, William; Howe, Tet Sen; Seow, Dennis Chuen Chai; Mamun, Kaysar; Balasubramanian, Diraviyam; Varman, Surendra Doraiswamy; et al. (Frontiers in Rehabilitation Sciences, 2023)
Due to an aging population, the rising prevalence and incidence of hip fractures and the associated health and economic burden present a challenge to healthcare systems worldwide. Studies have shown that there is often a complex interplay of physiological, psychological, and social factors that affect the recovery trajectories of older adults with hip fractures that often complicate the recovery process. This research aims to actively engage stakeholders (including doctors, physiotherapists, hip fracture patients, and caregivers) using the systems modeling methodology of Group Model Building (GMB) to elicit the factors that promote or inhibit hip fracture recovery, incorporating a feedback perspective to inform system-wide interventions. Hip fracture stakeholder engagement was facilitated through the Group Model Building approach in a two-half-day workshop of 25 stakeholders. This approach combined different techniques to develop a comprehensive qualitative whole-system view model of the factors that promote or inhibit hip fracture recovery. A conceptual qualitative model of the dynamics of hip fracture recovery was developed that draws on stakeholders’ personal experiences through a moderated interaction. Stakeholders identified four domains (i.e., expectation formation, rehabilitation, affordability/availability, and resilience building) that play a significant role in the hip fracture recovery journey.